Method for manufacturing aluminum alloy part

By selecting the appropriate addition elements and thermal treatment schemes in aluminum alloy, the problem of folding between the mechanical strength and conductivity of aluminum alloy manufacturing medium -sized aluminum alloy is solved, and the manufacturing of aluminum alloy parts with high conductivity and high hardness.

CN119384324APending Publication Date: 2025-01-28C TEC CONSTELLIUM TECH CENT
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380045797.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-06-09
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

It is difficult for existing aluminum alloys to achieve a good compromise between mechanical strength and electrical conductivity in the additive manufacturing process, and pure aluminum has high conductivity but low mechanical strength, and adding added elements will lead to contradictory effects.

Method used

Through wisely selection of adding elements, it is determined to be composed of aluminum alloys used for additive manufacturing, which includes ZR, HF, ER and other elements to ensure that the total amount of added elements exceeds 3%, and appropriate thermal treatment after manufacturing to increase the conductivity and the conductivity and the electrical rate and hardness.

Benefits of technology

In the case of no heat treatment, obtaining aluminum alloy parts with excellent mechanical properties and high conductivity, avoiding the deformation risk brought by heat treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384324A_ABST
    Figure CN119384324A_ABST
Patent Text Reader

Abstract

The invention relates to a method for manufacturing a part (20), said method comprising forming successive layers of metal (201... 20n) stacked on top of each other, each layer being formed by depositing a filler metal (15, 25), supplying energy to the filler metal, melting the filler metal, and forming said layer by solidification, said method being characterized in that the filler metal (15, 25) is formed on the surface of the part (20). 25) is an aluminum alloy comprising the following alloying elements (in% by weight):-at least one alloying element selected from the group consisting of Zr, Hf and Er, the respective and total weight fractions thereof being greater than or equal to 0.30; -at least one alloying element selected from the group consisting of Co, La, Ce, mixtures of rare earth metals, W, Ta, Mo and Nb, in each and in total weight fraction of at least 0.10; the weight percentages are respectively less than 5.00%; the total weight fraction is less than 7.00%; -optionally Fe, Ni, Si, Cu, Ag, Sc, Cr, V, Ti, Mn, Mg, Zn, Li, Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In, Sn and impurities; and the balance of aluminum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technical field of the present invention relates to a method for manufacturing a part made of aluminum alloy using additive manufacturing technology. Background Art

[0002] Additive manufacturing techniques have been developed since the 80s. They consist of forming parts by adding material, as opposed to machining techniques that aim to remove material. Previously limited to prototyping, additive manufacturing can now be used to manufacture industrial products, including metal parts, in a mass-produced manner.

[0003] The term "additive manufacturing" is defined according to the French standard XP E67-001 as "a collection of methods that allow the manufacture of physical objects, layer by layer, based on digital objects, by adding material". Additive manufacturing is also defined in the standard ASTM F2792 (January 2012). Different additive manufacturing methods are also defined and described in the standard ISO / ASTM 17296-1. The preparation of aluminum parts with low porosity by means of additive manufacturing has been described in document WO2015006447. Usually, successive layers are applied by applying a so-called filler material and then melting or sintering the filler material using an energy source of the laser beam, electron beam, plasma torch or arc type. Whatever the additive manufacturing method applied, the thickness of each added layer is tens or hundreds of micrometers.

[0004] Other additive manufacturing methods may also be used. For example, and without limitation, melting or sintering of a filler material in powder form may be mentioned. This may include laser melting or sintering. Patent application US20170016096 describes a method for manufacturing parts by local melting obtained by exposing a powder to an energy beam of the electron beam or laser beam type, which is also named by the Anglo-Saxon acronym LPBF, which stands for "Laser Powder Bed Fusion", or "EBM", which stands for "Electron Beam Melting".

[0005] The mechanical properties of aluminum parts obtained by additive manufacturing depend on the alloy forming the filler metal, and more specifically on its composition, as well as on the heat treatment applied after the implementation of additive manufacturing.

[0006] The applicant has identified an alloy composition which, when used in an additive manufacturing method, makes it possible to obtain parts having excellent mechanical properties without having to carry out heat treatments such as solution treatment and quenching. In addition, the parts used are characterized by favorable thermal or electrical conductivity. This good compromise between mechanical properties and thermal conductivity allows a wide range of application possibilities for these parts.

[0007] For aluminum alloys, pure aluminum generally obtains the maximum electrical conductivity or thermal conductivity. However, the mechanical strength of pure aluminum is low, which limits its field of use. In order to improve the mechanical strength of pure aluminum, the content of additive elements can be increased. Conversely, in order to improve the electrical conductivity of aluminum alloys, the content of additive elements other than aluminum can be limited. Therefore, changes in the total content of additive elements affect the conductivity and mechanical strength of aluminum alloys in a contradictory way. Therefore, it is difficult to design an aluminum alloy with a good compromise between mechanical strength and electrical conductivity.

[0008] Pure aluminum powder can be used as a reducing agent in solid propellant fuels for aerospace thrusters. Therefore, in some countries, aluminum powders with more than 97% aluminum are often considered dual-use goods (DUG) requiring an export license. This classification represents a constraint that may hinder the commercialization of some aluminum powders with more than 97% aluminum intended for additive manufacturing methods (such as LPBF). Therefore, it seems more advantageous to develop solutions with less than 97% aluminum (i.e. a total amount of added elements exceeding 3%). This condition makes the design of the alloy even more difficult, especially when one wants to maintain an acceptable minimum conductivity of 25MS / m (which corresponds to the reference conductivity value of alloy 6061 in metallurgical state T6).

[0009] According to one variant of the invention, the Applicant has identified, by judicious selection of additive elements, aluminium alloy compositions intended for additive manufacturing methods (particularly LPBF), which contain a total amount of additive elements exceeding 3% and have an electrical conductivity higher than 25 MS / m after post-manufacturing heat treatment.

[0010] According to another variant of the invention, the Applicant has identified, by judicious choice of added elements, aluminium alloy compositions intended for use in additive manufacturing methods (particularly LPBF) which allow, after post-manufacturing heat treatment, to maintain an electrical conductivity above 25 MS / m while maximizing the hardness (Knoop hardness HK 0.05, above 105). Summary of the invention

[0011] A first object of the invention is a method for manufacturing a part, comprising forming successive metal layers superposed on one another, each layer being formed by depositing a filler metal which melts after energy input and forms said layer when solidifying, said method being characterized in that said filler metal is an aluminum alloy containing the following alloying elements (in percentages by weight):

[0012] - at least one alloying element chosen from Zr, Hf and Er, the mass fraction of which is individually and in total greater than or equal to 0.30%, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%;

[0013] - at least one alloying element selected from Co, La, Ce, rare earth metal mixture, W, Ta, Mo and Nb, the mass fraction of which is at least 0.10%, preferably at least 0.25%, more preferably at least 0.50% each and in total; and the mass fraction of which is less than 5.00%, preferably less than 4.00%, preferably less than 3.00% each and in total

[0014] 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%; - optionally Fe, its mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than

[0015] Less than 1.00%, preferably less than 0.50%;

[0016] -Optionally Ni, with a mass fraction of less than 3.00%, preferably less than 2.00%, preferably less than

[0017] Less than 1.00%, preferably less than 0.50%;

[0018] - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are respectively

[0019] A total of 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, preferably 0.10 to 1.00%, preferably 0.10 to 0.70%;

[0020] - optionally Si, with a mass fraction of less than 3.00%, preferably less than 2.00%, preferably less than

[0021] 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%, preferably less than 0.20%, preferably less than 0.10%;

[0022] - Optionally Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than

[0023] less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%;

[0024] - optionally at least one alloying element selected from Cr, V, Ti and Mn, the mass percentage of which is

[0025] The total amount is less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than 0.50%, more preferably less than 0.10%, or even less than 0.05%.

[0026] to more preferably less than 0.05%;

[0027] - optionally Mg, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than

[0028] Less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.

[0029] Preferably less than 0.05%;

[0030] - optionally Zn, with a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than

[0031] Less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.

[0032] Preferably less than 0.05%;

[0033] - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0034] - optionally at least one element chosen from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and Sn, the mass fractions of which are each less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%,

[0035] Preferably less than or equal to 0.30%;

[0036] - Impurities: <0.05% individually and preferably <0.15% in total;

[0037] The rest is aluminum.

[0038] A second object of the invention is a method for manufacturing a part, comprising forming successive metal layers superposed on one another, each layer being formed by depositing a filler metal which melts after energy input and forms said layer when solidifying, said method being characterized in that said filler metal is an aluminum alloy containing the following alloying elements (in percentages by weight):

[0039] - at least one alloying element chosen from Zr, Hf and Er, the mass fraction of which is individually and in total greater than or equal to 0.30%, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%;

[0040] -Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%;

[0041] - optionally at least one alloying element selected from Co, La, Ce, rare earth metal mixtures, W, Ta, Mo and Nb, the mass fractions of which are each and in total at least 0.10%, preferably at least 0.25%, more preferably at least 0.50%; and the mass fractions of which are each less than 5.00%, preferably less than 4.00%, preferably less than 3.00%; and the mass fractions of which are in total less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%;

[0042] - optionally Fe, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%;

[0043] - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%;

[0044] - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%,

[0045] Preferably 0.10 to 1.00%, preferably 0.10 to 0.70%;

[0046] - optionally Si, the mass fraction of which is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%,

[0047] Preferably less than 0.20%, preferably less than 0.10%;

[0048] - optionally at least one alloying element chosen from Cr, V, Ti and Mn, the mass fractions of which are each less than 0.50%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%, more preferably less than 0.05% and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than 0.50%, more preferably less than 0.10%, even more preferably less than 0.05%;

[0049] - optionally Mg, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0050] - optionally Zn, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0051] - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0052] - optionally at least one element chosen from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and Sn, the mass fractions of which are each less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%,

[0053] Preferably less than or equal to 0.30%;

[0054] - Impurities: <0.05% individually and preferably <0.15% in total;

[0055] The rest is aluminum.

[0056] In particular, each layer may describe a pattern defined by the digital model. The pattern of each layer is a two-dimensional shape corresponding to a cross section of the final three-dimensional object.

[0057] According to one embodiment, the filler metal is in the form of a powder, which is exposed to a light beam or charged particles, causing local melting and then solidification to form a solid layer. According to another embodiment, the filler metal originates from a filler wire, which is exposed to a heat source, such as an electric arc, causing local melting and then solidification to form a solid layer.

[0058] A third object of the present invention is a metal part obtained by the method according to the first or second object of the present invention.

[0059] A fourth object of the present invention is a filler material, in particular a filler wire or powder, intended for use as a filler material in an additive manufacturing method, said filler material being characterized in that it consists of an aluminum alloy containing the following alloying elements (in weight %):

[0060] - at least one alloying element chosen from Zr, Hf and Er, the mass fraction of which is individually and in total greater than or equal to 0.30%, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%;

[0061] - at least one alloying element selected from Co, La, Ce, rare earth metal mixture, W, Ta, Mo and Nb, the mass fraction of which is at least 0.10% each and in total, preferably at least 0.25%, more preferably at least 0.50%; and the mass fraction of which is less than 5.00% each, preferably less than 4.00%, preferably less than 3.00%; and the mass fraction of which is less than 7.00% each, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00% in total;

[0062] - optionally Fe, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%;

[0063] - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%;

[0064] - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%,

[0065] Preferably 0.10 to 1.00%, preferably 0.10 to 0.70%;

[0066] - optionally Si, the mass fraction of which is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%,

[0067] Preferably less than 0.20%, preferably less than 0.10%;

[0068] - optionally Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%,

[0069] Preferably less than 0.20%, preferably less than 0.10%;

[0070] - optionally at least one alloying element chosen from Cr, V, Ti and Mn, the mass fractions of which are each less than 0.50%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%, more preferably less than 0.05% and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than 0.50%, more preferably less than 0.10%, even more preferably less than 0.05%;

[0071] - optionally Mg, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0072] - optionally Zn, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0073] - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0074] - optionally at least one element chosen from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and Sn, the mass fractions of which are each less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%,

[0075] Preferably less than or equal to 0.30%;

[0076] - Impurities: <0.05% each and <0.15% in total;

[0077] The rest is aluminum.

[0078] A fifth object of the invention is a filler material, in particular a filler wire or powder, intended for use as a filler material in an additive manufacturing method, said filler material being characterized in that it consists of an aluminum alloy and contains the following alloying elements (in weight %):

[0079] - at least one alloying element chosen from Zr, Hf and Er, the mass fraction of which is individually and in total greater than or equal to 0.30%, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%;

[0080] -Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%;

[0083] - optionally at least one alloying element selected from Co, La, Ce, rare earth metal mixtures, W, Ta, Mo and Nb, the mass fractions of which are each and in total at least 0.10%, preferably at least 0.25%, more preferably at least 0.50%; and the mass fractions of which are each less than 5.00%, preferably less than 4.00%, preferably less than 3.00%; and the mass fractions of which are in total less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%;

[0086] - optionally Fe, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%;

[0088] - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%;

[0090] - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, preferably 0.10 to 1.00%, preferably 0.10 to 0.70%;

[0092] - optionally Si, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%, preferably less than 0.20%, preferably less than 0.10%;

[0094] - optionally at least one alloying element chosen from Cr, V, Ti and Mn, the mass fractions of which are each less than 0.50%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%, more preferably less than 0.05% and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than 0.50%, more preferably less than 0.10%, even more preferably less than 0.05%;

[0097] - optionally Mg, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0100] - optionally Zn, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0103] - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%;

[0104] - optionally at least one selected from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi,

[0105] The elements Ca, P, B, In and Sn, each of which has a mass fraction less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm, and a total of less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%,

[0106] Preferably less than or equal to 0.30%;

[0107] - Impurities: <0.05% each and <0.15% in total;

[0108] The rest is aluminum.

[0109] The aluminum alloy forming the filler material may have the characteristics described in relation to the first aspect of the present invention.

[0110] The filler material may be in the form of a powder. The powder may be such that at least 80% of the particles making up the powder have an average size in the range of 5 to 200 μm, preferably 5 to 150 μm, preferably 5 to 25 μm, or 20 to 60 μm or 20 to 80 μm or 20 to 90 μm or 20 to 100 μm or 20 to 110 μm or 20 to 120 μm.

[0111] In case the filler material is in the form of a metal wire, the diameter of the metal wire may in particular be 0.5 mm to 3 mm, preferably 0.5 mm to 2 mm, more preferably 1 mm to 2 mm.

[0112] The sixth object of the present invention is the use of the powder or filler wire described above and in the rest of this specification for a manufacturing method, wherein the manufacturing method is selected from: EBM (electron beam melting), cold spraying (CSC or CS), laser melting deposition (LMD), additive friction manufacturing (AFS or AFSD, or FSAM, or FS), spark plasma sintering (FAST) or rotary friction welding (IRFW), preferably cold spraying (CSC).

[0113] Other advantages and features will emerge more clearly from the following description of specific embodiments of the invention, provided as non-limiting examples, and illustrated in the figures listed hereinafter. BRIEF DESCRIPTION OF THE DRAWINGS

[0114] [ Figure 1 ] Figure 1 is a schematic diagram illustrating the LPBF type additive manufacturing method.

[0115] [ Figure 2 ] Figure 2 is a schematic diagram illustrating a WAAM type additive manufacturing method.

[0116] [ Figure 3 ] Figure 3 is a schematic diagram of a strip after laser reflow according to an embodiment.

[0117] [ Figure 4 ] Figure 4 It is a schematic diagram of the Knoop hardness measurement test. DETAILED DESCRIPTION

[0118] Unless otherwise stated, in this manual:

[0119] - The naming of aluminum alloys complies with the nomenclature of The Aluminum Association;

[0120] - The content of chemical elements is reported in % and represents mass fraction. The symbol x%-y% means greater than or equal to x% and less than or equal to y%.

[0121] Impurities are understood to be chemical elements that are not intentionally present in the alloy.

[0122] Figure 1 The operation of an additive manufacturing method of the selective laser melting type (laser powder bed melting or LPBF) is represented diagrammatically. A filler metal 15 is arranged in the form of a powder on a support 10. An energy source, in this case a laser source 11, emits a laser beam 12. The laser source is coupled to the filler material via an optical system 13, the movement of which is determined according to a numerical model M. The laser beam 12 propagates along a propagation axis Z and moves according to a plane XY, describing a pattern according to the numerical model. For example, the plane is perpendicular to the propagation axis Z. The interaction of the laser beam 12 with the powder 15 results in selective melting of the powder 15, which then solidifies, thereby forming layers 201 ... 20 n When one layer has been formed, it is covered with powder 15 of filler metal and another layer is formed superimposed on the previously prepared layer. For example, the thickness of the melted and solidified layer may be 10 to 250 μm, such as 30 μm, 60 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.

[0123] The increase in layer thickness may be beneficial for increasing productivity during printing and limiting the susceptibility to thermal cracking associated with residual stresses during part manufacturing and / or post-manufacturing heat treatment. The increase in layer thickness may be accompanied by adaptive changes in laser power, vector deviation (the distance between two consecutive laser passes) and laser scanning speed to ensure complete melting of each powder layer under optimal conditions. For example, the layer thickness may be 60 to 250 μm, preferably 80 to 200 μm, preferably 90 to 180 μm, preferably 100 to 180 μm, preferably 110 to 170 μm, preferably 120 to 160 μm.

[0124] For aluminium alloys, the support 10 or the tray can be heated to a preheating temperature T of up to 500°C. Typically, machines currently available on the market can heat the tray up to 200°C. For example, the heating temperature of the tray (= preheating temperature T) can be about 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C. Typically, heating the tray enables to reduce the humidity in the powder bed and at the same time reduce the residual stresses on the part during manufacturing. The humidity level at the powder bed level seems to have a direct influence on the porosity of the final part. In fact, it seems that the higher the humidity of the powder, the higher the porosity of the final part. It should be noted that heating the tray is one of the existing possibilities for implementing thermal additive manufacturing. However, the invention cannot be limited to the use of only this heating method. All other other heating methods that allow the implementation of this preheating step can be used in the context of the invention for heating and controlling the temperature, such as infrared lamps. Therefore, the method according to the invention can be carried out at a preheating temperature T of up to 500°C.

[0125] For some compositions, the inventors have noticed that when the preheating temperature T of the powder bed is less than or equal to 160°C and greater than or equal to 25°C, the part has better resistance to thermal cracking associated with residual stresses. Preferably, the preheating of the powder bed can be carried out at a preheating temperature T less than or equal to 140°C, or, better yet, less than or equal to 130°C. The preheating temperature T is higher than room temperature. The preferred preheating temperature range T of the powder bed is: 25°C≤T≤160°C, preferably 30°C≤T≤150°C, preferably 50°C≤T≤150°C, preferably 50°C≤T≤140°C, preferably 60°C≤T≤140°C, preferably 70°C≤T≤135°C, preferably 80°C≤T≤130°C.

[0126] According to an alternative, the preheating temperature T corresponds to the conditions under which effective expansion can be obtained. The preheating temperature range T may then be 300° C. to 500° C., preferably 300 to 400° C., preferably 300 to 350° C. It is believed that in this preheating temperature range T, the manufacturing conditions of the part produce less residual stress. According to this alternative, the post-manufacturing heat treatment expansion is also relevant, as described later in this specification.

[0127] Powders may have at least one of the following characteristics:

[0128] - an average particle size of 5 to 200 μm, preferably 5 to 150 μm, preferably 5 to 25 μm,

[0129] or 20 to 60 μm, or 20 to 80 μm, or 20 to 90 μm, or 20 to 100 μm, or 20 to 110 μm, or 20 to 120 μm. The data values ​​mean that at least 80% of the particles have an average particle size within the specified range.

[0130] - Spherical shape. For example, the sphericity of a powder can be determined using a particle morphology analyzer.

[0131] - Good castability. For example, the castability of the powder can be determined according to standard ASTM B213 or standard ISO 4490:2018. According to standard ISO 4490:2018, the flow time is preferably shorter than 50 seconds.

[0132] - Low porosity, preferably 0 to 5 vol.%, more preferably 0 to 2 vol.%, even more preferably 0 to 1 vol.%, more preferably 0 to 0.5 vol.%. In particular, the porosity can be determined by analyzing images of optical micrographs or by the helium pycnometer method (see standard ASTM B923).

[0133] The absence or presence of a small amount (less than 10% by volume, preferably less than 5% by volume) of small particles (1 to 20% of the average particle size of the powder), so-called satellite particles, which adhere to the larger particles.

[0134] Implementation of this approach allows high throughput manufacturing of parts, reaching and even exceeding 200 cm by laser. 3 / h.

[0135] Furthermore, the Applicant has observed that the application of a post-manufacturing heat treatment of the quenching type may cause deformations of the part due to the sudden change in temperature. Usually, due to the large size of the part, its deformation is even more significant. However, the advantage of the additive manufacturing method is to specifically obtain parts whose shape after manufacturing is permanent or quasi-permanent. Therefore, the occurrence of significant deformations of the part due to post-manufacturing heat treatment should be avoided. "Quasi-permanent" should be understood as the possibility of finishing the part after its manufacturing: the part manufactured by additive manufacturing is extended according to its final shape within the finishing allowance.

[0136] Having noted the above, the Applicant has sought an alloy composition for forming the filler material that allows obtaining acceptable mechanical and electrical properties without having to apply a heat treatment after layer formation (i.e. after the final part has been formed), which heat treatment could cause deformations. In particular, the aim is to avoid heat treatments involving sudden changes in temperature. The invention thus allows obtaining parts with satisfactory mechanical properties, in particular in terms of yield strength, and conductivity by additive manufacturing. The filler material can be in the form of a wire or a powder, depending on the type of additive manufacturing method chosen.

[0137] The following elements can be used in aluminum alloys.

[0138] Zr, Hf and / or Er:

[0139] According to the invention, the elements Zr, Hf and / or Er are present in the aluminum alloy in a mass fraction, each and in total, greater than or equal to 0.30%, preferably 0.30 to 2.50%, preferably 0.40 to 2.00%, more preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%. According to one variant, the mass fraction of the elements Zr, Hf and / or Er may be greater than or equal to 0.30%, 0.40%, 0.50%, 0.60%, 0.70% or 0.80%. According to one variant, the mass fraction of the elements Zr, Hf and / or Er may be less than or equal to 2.50%, 2.40%, 2.30%, 2.20%, 2.10%, 2.00%, 1.90%, 1.80%, 1.70%, 1.60%, 1.50%, 1.40% or 1.30%.

[0140] These elements have high solid solubility in the original state of manufacture. Therefore, their addition can significantly reduce the conductivity in the original state. However, adding a post-manufacturing heat treatment, for example at a temperature of 300 to 450°C for 0.5 to 10 hours, can allow to significantly reduce their content in solid solution by forming Al3X type hardening dispersed phases (X = Zr or Hf or Er). During the heat treatment, the formation of these dispersed phases can allow to increase both hardness and conductivity relative to the original state.

[0141] These elements may also allow for control of the grain structure during laser melting by promoting the appearance of equiaxed grains.

[0142] Furthermore, the presence of Zr, Hf and / or Er in the alloy can give the alloy good processing properties, a term corresponding to the English name "processability", which refers to the ability of the alloy to be formed by additive manufacturing methods. This can be manifested at the level of the parts manufactured by additive manufacturing as a quasi-absence of defects such as cracks, as well as a low porosity.

[0143] Co, La, Ce, mischmetal, W, Ta, Mo and / or Nb:

[0144] According to the present invention, the elements Co, La, Ce, rare earth metal mixture, W, Ta, Mo and / or Nb may be present in the aluminum alloy, and their mass fractions are each at least 0.10%, preferably at least 0.25%, more preferably at least 0.50% in total; and their mass fractions are each less than 5.00%, preferably less than 4.00%, preferably less than 3.00%; and their mass fractions are less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00% in total.

[0145] These elements can allow for increased mechanical strength of the alloy through solid solution and / or through dispersed phases that may form during part fabrication or during post-fabrication heat treatment. These elements have very low solid solubility in aluminum. Adding these elements can harden the alloy without significantly negatively affecting conductivity.

[0146] Fe:

[0147] According to the present invention, the aluminum alloy may contain element Fe, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%. According to a variant, the aluminum alloy may contain element Fe, whose mass fraction is greater than 500ppm, or greater than 0.10%, or greater than 0.15%, or greater than 0.20%, or greater than 0.30%, or greater than 0.40%.

[0148] This element can allow for an increase in the mechanical strength of the alloy through solid solution and / or through dispersed phases that may form during part fabrication or during post-fabrication heat treatment. This element has a low solid solubility in aluminum. The addition of this element can harden the alloy without significantly negatively affecting conductivity.

[0149] Ni:

[0150] According to the invention, the element Ni may be present in the aluminum alloy in a mass fraction of less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%. According to one variant, the element Ni may be present in the aluminum alloy in a mass fraction greater than 500 ppm, or greater than 0.10%, or greater than 0.15%, or greater than 0.20%, or greater than 0.30%, or greater than 0.40%.

[0151] This element can allow the mechanical strength of the alloy to be increased through solid solution and / or through dispersed phases that may form during part manufacturing or during post-manufacturing heat treatment. This element has a low solid solubility in aluminum. The addition of this element can harden the alloy without significantly affecting conductivity.

[0152] Cu and / or Ag:

[0153] According to the invention, the elements Cu and / or Ag may be present in the aluminum alloy in a mass fraction of 0.10 to 3.00% individually and in total, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, preferably 0.10 to 1.00%, preferably 0.10 to 0.70%.

[0154] These elements may allow for an increase in the mechanical strength of the alloy through solid solution and / or hardening precipitates that may form during part fabrication or during post-fabrication heat treatment.

[0155] Si:

[0156] According to the invention, the aluminum alloy may contain element Si in an amount less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50% by mass; in one embodiment, the Si content is less than 0.30%, preferably less than 0.20%. According to a variant, the aluminum alloy may contain element Si in an amount greater than 500 ppm by mass, or greater than 0.10%, or greater than 0.15%.

[0157] Addition of Si in the presence of Zr results in the formation of a coarse AlZrSi phase which limits the hardening ability of Zr after heat treatment.

[0158] Sc:

[0159] According to the present invention, the element Sc may be present in the aluminum alloy, and its mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%; and preferably its mass fraction is greater than 500ppm, preferably greater than 0.10%, preferably greater than 0.15%, preferably greater than 0.20%.

[0160] This element may have the same technical effect as the elements Zr, Hf and Er. On the other hand, according to a variant of the invention, the inventors have noticed that a good compromise between mechanical properties and conductivity can also be obtained, preferably after heat treatment, by replacing at least part of the group of elements Co, La, Ce, mischmetal, W, Ta, Mo and / or Nb with Sc in mass fractions as described above.

[0161] Cr, V, Ti and / or Mn:

[0162] According to the invention, the elements Cr, V, Ti and / or Mn may be present in the aluminum alloy, each of which has a mass fraction less than 0.50%, preferably less than 0.30%, preferably less than 0.20%, and a total of less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than 0.50%. According to one variant, the elements Cr, V, Ti and / or Mn may be present in the aluminum alloy, each of which has a mass fraction greater than 300 ppm, or greater than 500 ppm, or greater than 0.10%.

[0163] These elements may allow to increase the mechanical strength of the alloy through solid solution and / or through dispersed phases that may be formed during part manufacturing or during post-manufacturing heat treatment. However, the solid solubility of these elements in aluminum is very high and they may have a negative impact on conductivity. Therefore, according to one embodiment, the addition of these elements should preferably be avoided.

[0164] Mg, Zn and / or Li:

[0165] According to the invention, the aluminum alloy may contain elements Mg, Zn and / or Li, each of which is less than 2.00% by mass and in total, preferably less than 1.00% by mass, preferably less than 0.50% by mass, more preferably less than 0.30% by mass. According to one variant, the aluminum alloy may contain elements Cr, V, Ti and / or Mn, each of which is greater than 500 ppm by mass and in total, or greater than 0.10% by mass, or greater than 0.20% by mass.

[0166] These elements can allow to improve the mechanical strength of the alloy through solid solution. However, these elements are sensitive to evaporation during laser melting, which may lead to smoke formation and instability of the molten pool. Excessive addition of these elements can significantly reduce electrical conductivity. Therefore, according to one embodiment, the addition of these elements should preferably be avoided.

[0167] Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and / or Sn:

[0168] According to the invention, the elements Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and / or Sn may be present in the aluminum alloy in a mass fraction each less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%, preferably less than or equal to 0.30%. According to one variant, the elements Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, Ca, P, B, In and / or Sn may be present in the aluminum alloy in a mass fraction each and in total greater than 100 ppm, or greater than 300 ppm, or greater than 500 ppm.

[0169] These elements may allow to increase the mechanical strength of the alloy through solid solution and / or through dispersed phases that may be formed during part manufacturing or during post-manufacturing heat treatment. However, excessive addition of these elements may reduce the conductivity of the alloy, and for this reason, according to one embodiment, their addition is preferably done in a mass fraction of less than 700 ppm each.

[0170] Preferably, different optional elements may be present in the aluminum alloy, with a mass fraction of less than 15.00%, or less than 13.00%, or less than 11.00%, or less than 10.00%, or less than 9.00%, or less than 8.00%, or less than 7.00%, or less than 6.00%, or less than 5.50%.

[0171] It should be noted that, preferably, the alloy according to the present invention is not an AA6xxx alloy, since there are no simultaneous additions of Si and Mg greater than 0.2%.

[0172] The method may include applying at least one heat treatment after forming the layers, i.e. after forming the final part. Such treatment is also referred to as post-fabrication or post-processing heat treatment. Post-fabrication heat treatment may be or include tempering or annealing. It may also include solution treatment and quenching, even if they are preferably avoided. It may also include hot isostatic pressing.

[0173] According to a first variant, a post-manufacturing heat treatment may be performed in order to favour the mechanical properties:

[0174] - at a temperature T′ higher than 400° C., in which case the duration of the post-production heat treatment is from 0.1 h to 50 h, preferably from 0.1 h to 10 h;

[0175] - or at a temperature T' of 300 to 400°C, in which case the duration of the post-production heat treatment is 0.1 h to 200 h.

[0176] According to a second variant, in order to favour thermal or electrical conductivity, a post-manufacturing heat treatment may be carried out at a temperature T′ higher than or equal to 350° C. or 400° C., for a duration ranging from 0.1 h to 200 h, in order to obtain an optimum thermal or electrical conductivity.

[0177] According to another variant, a two-step post-manufacturing heat treatment can allow the electrical conductivity to be maximized. These treatments consist firstly of a first step at a temperature T′1 above 450° C. for a duration of 0.1 h to 100 h, followed by a second step at a temperature T′2 between 300° C. and 450° C. for a duration of 0.1 h to 200 h.

[0178] According to another variant, a two-step post-manufacturing heat treatment can maximize the electrical conductivity and / or hardness. These treatments consist firstly of a first step at a temperature T′1 below 380° C. for a duration of 0.1 h to 200 h, followed by a second step at a temperature T′2 between 380° C. and 450° C. for a duration of 0.1 h to 200 h.

[0179] According to another variant, a three-step post-manufacturing heat treatment can maximize the electrical conductivity and / or hardness. These treatments consist first of a first step at a temperature T′1 of 250° C. to 450° C. for a duration of 0.1 h to 200 h, then a second step at a temperature T′2 above 450° C. for a duration of 0.1 h to 100 h, then a third step at a temperature T′3 of 250° C. to 450° C. for a duration of 0.1 h to 200 h.

[0180] Multi-step processing with more than three steps can also be considered.

[0181] According to one embodiment, the method may include hot isostatic pressing (HIP). In particular, the HIP treatment may allow for improved tensile properties and fatigue properties. Hot isostatic pressing may be performed before, after or instead of post-manufacturing heat treatment. Advantageously, hot isostatic pressing is performed at a temperature of 250° C. to 500° C., preferably 300° C. to 450° C., at a pressure of 500 to 3,000 bar, and for a duration of 0.5 to 100 hours.

[0182] According to an advantageous embodiment, the method does not comprise quenching after forming the layer, ie after forming the final part, or after heat treatment. Thus, preferably, the method does not comprise a step of quenching after solution treatment.

[0183] By means of a post-manufacturing heat treatment, the manufacturing is carried out by an additive manufacturing method, which allows the creation of expansion conditions, allowing the elimination of residual stresses and the precipitation of hardened phases. We also discussed thermal expansion. The inventors have observed that the preferred setpoint temperature T' for the post-manufacturing heat treatment is between 300°C and 500°C.

[0184] In particular, possible heat treatments and / or hot isostatic pressing allow to increase the hardness or yield strength and the electrical conductivity of the product obtained. However, it should be noted that generally the higher the temperature, the greater the increase in conductivity (electrical or thermal), thus compromising the mechanical strength.

[0185] According to one embodiment, in addition to the temperature T' of the post-manufacturing heat treatment, the temperature increase at the start of the post-manufacturing heat treatment is preferably as fast as possible. For example, during the temperature increase, the temperature increase rate ΔT' (commonly referred to as "heating rate" by those skilled in the art, in °C per minute or °C per second) is preferably higher than 5 °C per minute or higher than 10 °C per minute, or more preferably higher than 20 °C per minute, more advantageously higher than 40 °C per minute, and more advantageously higher than 100 °C per minute. "Heat increase" should be understood as the temperature rise to which the part is subjected during the post-manufacturing heat treatment. It seems that the best way is that the temperature increase is instantaneous, that is, the manufactured part is subjected to the post-manufacturing heat treatment setpoint temperature T' from the beginning of the post-manufacturing heat treatment. Instantaneous temperature increase can be obtained by placing the manufactured part in a hot furnace that has reached the setpoint temperature T', or by a rapid heating method of fluidized bed or molten salt bath type. Temperature increase can also be ensured by induction heating.

[0186] For the same temperature increase of the outside of the part, the variation of the temperature inside the part depends in particular on the heating medium (liquid or air or inert gas) and on the shape of the part. In particular, the temperature may be different over the thickness of the part or on the surface. This is why the temperature increase mentioned above corresponds to the temperature of the outside of the part. The combination of the preheating temperature T, the post-manufacturing heat treatment temperature T' and the heating rate ΔT' during the temperature increase of the post-manufacturing heat treatment within the above-mentioned numerical range allows to obtain a part with good resistance to thermal cracking.

[0187] According to another embodiment, suitable for structural hardening alloys, the formed part can be solution treated, followed by quenching and tempering and / or hot isostatic pressing. In this case, hot isostatic pressing can advantageously replace solution treatment.

[0188] However, the method according to the invention is advantageous because it preferably does not require a treatment comprising a solution treatment followed by a quench. In certain cases, a solution treatment can adversely affect the mechanical strength by contributing to the enlargement of dispersed phases or fine intermetallic phases. Preferably, the method according to the invention does not comprise a solution treatment and / or a quench, which is performed after the formation of the layer, i.e. after the formation of the final part, or after a post-manufacturing heat treatment.

[0189] According to one embodiment, optionally, the method according to the invention further comprises a mechanical processing treatment, and / or a chemical, electrochemical or mechanical surface treatment, and / or a vibration finishing. In particular, these treatments can be performed to reduce roughness and / or to improve corrosion resistance and / or to improve resistance to fatigue crack initiation.

[0190] Optionally, mechanical deformation of the part may be performed, for example after additive manufacturing and / or before heat treatment.

[0191] Although described in relation to an LPBF type additive manufacturing method, the method may also be applied to other WAAM (Wire plus Arc Additive Manufacturing) type additive manufacturing methods mentioned in relation to the prior art. Figure 2 Such an alternative is shown. An energy source 31, in this case a torch, forms an electric arc 32. In this arrangement, the torch 31 is held by a welding robot 33. The part 20 to be manufactured is arranged on a support 10. In this embodiment, the part to be manufactured is a wall extending along a transverse axis Z perpendicular to a plane XY defined by the support 10. Under the action of the electric arc 12, a filler wire 35 melts to form a weld. The welding robot is controlled by a digital model M. It is moved to form the different layers 201 ... 20 n , the layers are stacked one on top of another to form a wall 20, each layer corresponding to a weld. n It extends in the plane XY according to the pattern defined by the digital model M.

[0192] Preferably, the diameter of the filler wire is less than 3 mm. It may be 0.5 mm to 3 mm, and preferably 0.5 mm to 2 mm, or 1 mm to 2 mm. For example, it is equivalent to 1.2 mm.

[0193] In addition, other methods may be considered, such as but not limited to:

[0194] -Selective Laser Sintering (SLS);

[0195] -Direct Metal Laser Sintering (DMLS);

[0196] -Selective Heat Sintering (SHS);

[0197] -Electron Beam Melting (EBM);

[0198] -Laser Melting Deposition;

[0199] - Direct Energy Deposition (DED);

[0200] -Direct Metal Deposition (DMD);

[0201] - Direct Laser Deposition (DLD);

[0202] -Laser Deposition Technology;

[0203] -Laser Engineering Net Shaping;

[0204] -Laser Cladding Technology;

[0205] -Laser Freedom Manufacturing Technology (LFMT);

[0206] -Laser Metal Deposition (LMD);

[0207] -Cold Spray Consolidation (CSC);

[0208] - Additive Friction Stir (AFS or AFSD or FSAM or FS);

[0209] - Field Assisted Sintering Technology or spark plasma sintering (FAST or spark plasma sintering); or

[0210] -Inertia Rotary Friction Welding (IRFW).

[0211] The solution according to the invention is particularly suitable for cold spraying methods (so-called "cold spray"), in particular because the powder has a low hardness, which facilitates deposition. The part can then be hardened by hardening annealing (after heat treatment).

[0212] The solution according to the invention is particularly suitable for applications in the electrical, electronic and heat exchanger industries.

[0213] Experimental Examples

[0214] Example 1

[0215] The experimental alloy was cast in a copper mold using an induction type VC 650V machine to obtain an ingot with a height of 130 mm, a width of 95 mm and a thickness of 5 mm.

[0216] The alloys as described in Table 1 below have been tested by a rapid prototyping method. From the ingots obtained above, samples have been machined for scanning the surface with a laser, in the form of strips with dimensions of 60×22×3 mm. The strips were placed in an LPBF machine and the surface was scanned with a laser following the same scanning strategy and process conditions as for the LPBF method. In fact, it has been found that by this method it is possible to evaluate the capabilities of the alloys for the LPBF method, in particular the susceptibility to hot cracking, the hardness in the original state and after heat treatment, the electrical conductivity in the original state and after heat treatment.

[0217] Under the laser beam, the metal melts in a molten pool with a thickness of about 500 μm. After the laser pass, the metal cools rapidly, just like in the LPBF method. After the laser scan, a thin layer of about 500 μm thick on the surface melts and then solidifies. Due to the judicious choice of the scanning parameters, the properties of this layer of metal are close to those of the metal at the core of the part manufactured by LPBF. The surface of different samples was laser scanned by a 350 selective laser powder bed fusion (LPBF) machine. The laser source power was 400W, the vector deviation was 60μm, the scanning speed was 500mm / s, and the beam diameter was 65μm.

[0218] On each strip, two 5 mm x 35 mm rectangular surfaces were melted for hardness measurement, and one 15 mm x 18 mm rectangular surface was melted for conductivity measurement.

[0219] Figure 3 An example of a ribbon after laser reflow is shown. Mark 1 corresponds to the two melted rectangular surfaces used for hardness measurements, mark 2 corresponds to the remelted rectangular surface used for conductivity measurements, and mark 3 corresponds to the non-remelted surface of the initial ribbon.

[0220] After each test, the same samples were subjected to a thermal post-treatment of the annealing type at 400°C for 1, 4 or 7 hours.

[0221] Knoop hardness measurement

[0222] Hardness is the main property of an alloy. In fact, if the hardness of the layer remelted by scanning the surface with a laser is high, the part made of the same alloy will have a high yield strength.

[0223] To evaluate the hardness of the remelted layer, the strips obtained above were cut in a plane perpendicular to the direction of the laser path and subsequently polished. After polishing, the hardness of the remelted layer was measured. The hardness measurement used a Durascan model device provided by Struers. To ensure a sufficient distance between the indentation and the edge of the sample, the 50g Knoop hardness method was chosen, in which the large diagonal of the indentation was placed parallel to the plane of the remelted layer. 30 indentations were arranged at the mid-thickness of the remelted layer. Figure 4 An example of hardness measurement is shown. Mark 4 corresponds to the remelted layer, mark 5 corresponds to the Knoop hardness indentation, and mark 6 corresponds to the non-remelted area.

[0224] The hardness was measured according to the Knoop hardness scale with a load of 50 g after the laser treatment (in the original state) and after additional heat treatment at 400°C for different lengths of time, allowing in particular to assess the hardenability of the alloy during the heat treatment and the influence of a possible HIP treatment on the mechanical properties and the electrical conductivity.

[0225] Electrical conductivity measurement

[0226] Based on the fact that the electrical conductivity develops similarly to the thermal conductivity, electrical conductivity measurements were performed on a 15 mm x 18 mm remelted rectangular surface of each strip. The linear dependence between thermal conductivity and electrical conductivity according to the Wiedemann-Franz law has been verified by Hatch in the publication "Aluminum properties and physical metallurgy" ASM Metals Park, OH, 1988. The electrical conductivity measurements were performed in the plane of the large face of the strip at the center of the remelted surface (plane parallel to the direction of the laser path). The electrical conductivity measurements were performed in the original state (without post-manufacturing heat treatment) and after heat treatment at 400°C for different lengths of 1 hour, 4 hours or 7 hours. An average of 5 different measurements was performed under each condition.

[0227] The conductivity measurements were carried out at a temperature of about 20° C. using a Foerster Sigmatest 2.069 measuring instrument at a frequency of 960 kHz. The choice of this frequency allowed the conductivity to be measured to a depth limited to the remelted region of the strip.

[0228] The compositions of the experimental aluminum alloys are reported in Table 1 below, in units of weight percent.

[0229] Two reference alloys were used:

[0230] - Composition No. 14, which includes aluminum, and the following alloying elements: Fe (0.5%) and Zr (1.2%);

[0231] - Composition No. 22, which includes aluminum, and the following alloying elements: Fe (1%) and Zr

[0232] (1.2%).

[0233] [Table 1]

[0234] Composition No. type Fe Zr Cu Si Ce La Co Sc 1 invention 0.50 1.20 2.00 2 invention 0.50 1.20 2.00 3 invention 0.50 1.20 1.00 1.00 4 invention 1.00 1.20 1.50 5 invention 1.00 1.20 1.50 6 invention 1.00 1.20 0.75 0.75 7 invention 1.20 2.50 8 invention 1.20 2.50 9 invention 1.20 1.25 1.25 10 invention 1.00 1.20 0.30 1.20 11 invention 1.00 1.20 0.30 1.20 12 invention 1.00 1.20 0.30 0.60 0.60 13 invention 0.50 1.20 1.50 1.50 14 refer to 0.50 1.20 15 invention 0.50 1.20 0.30 1.70 16 invention 0.50 1.20 0.30 1.70 17 invention 0.50 1.20 1.70 1.70 18 invention 0.50 1.20 0.50 1.70 19 invention 0.50 1.20 0.50 1.70 20 invention 1.20 2.20 21 invention 1.00 1.20 1.50 22 refer to 1.00 1.20 23 invention 1.00 0.60 0.60

[0235] Table 2 below shows the Knoop hardness (HK 0.05) and electrical conductivity values ​​measured for each alloy in the original state (0 hours heat treatment) and after laser reflow.

[0236] [Table 2]

[0237]

[0238] Table 3 below shows the Knoop hardness (HK 0.05) and electrical conductivity values ​​measured for each alloy after laser reflow and after annealing at 400° C. for 1 hour after laser reflow.

[0239] [Table 3]

[0240]

[0241]

[0242] Table 4 below shows the Knoop hardness (HK 0.05) and electrical conductivity values ​​measured for each alloy after laser reflow and after annealing at 400°C for 4 hours after laser reflow.

[0243] [Table 4]

[0244]

[0245] Table 5 below shows the Knoop hardness (HK 0.05) and electrical conductivity values ​​measured for each alloy after laser reflow and after annealing at 400° C. for 7 hours following laser reflow.

[0246] [Table 5]

[0247]

[0248]

[0249] The results of Tables 2, 3, 4 and 5 show that for all tested solutions the conductivity and hardness values ​​are lowest in the original state. An additional heat treatment at 400°C allows to increase the conductivity and Knoop hardness (HK 0.05) compared to the original state.

[0250] For all tested protocols, the maximum conductivity was obtained after 7 hours at 400°C.

[0251] For all tested solutions, the maximum hardness is obtained after 1 hour to 7 hours of treatment at 400° C. For all tested solutions, the duration for which the hardness is maximized appears to be between 0.5 hours and 10 hours.

[0252] Increasing the duration of the heat treatment at 400°C to more than 10 hours allows further improvement of the thermal conductivity, but reduces the hardness.

[0253] Therefore, the final heat treatment can be selected according to the intended application.

[0254] For alloys containing Sc, such as, for example, Alloy No. 23, a heat treatment temperature of 300 to 400°C for 0.5 to 10 hours may be optimal for maximizing hardness. For example, a temperature of 325°C for 4 hours.

[0255] Tables 4 and 5 show that several versions of the present invention are able to provide higher Knoop hardness (HK0.05) than Alloy No. 23 while maintaining electrical conductivity values ​​above 25 MS / m.

[0256] Tables 4 and 5 show that several solutions of the present invention are able to provide higher Knoop hardness (HK0.05) than Alloy No. 23 while maintaining electrical conductivity values ​​above 25 MS / m and a total content of added elements above 3%.

[0257] The experimental values ​​obtained in the above examples enable the following formula to be determined.

[0258] Preferably, according to the first variant of the process according to the invention, after post-treatment at 400° C. for 4 hours:

[0259] - an electrical conductivity in MS / m higher than 20, preferably higher than 22, preferably higher than 23,

[0260] Preferably higher than 24, preferably higher than 25; and

[0261] -The electrical conductivity in MS / m and hardness HK 0.05 conform to the following relationship:

[0262] 38<[conductivity+(0.137×hardness)]<47; and preferably

[0263] 39<[conductivity+(0.137×hardness)]<46; and more preferably

[0264] 40<[conductivity+(0.137×hardness)]<45.

[0265] Preferably, according to the second variant of the process according to the invention, after post-treatment at 400° C. for 7 hours:

[0266] - an electrical conductivity in MS / m higher than 20, preferably higher than 22, preferably higher than 23,

[0267] Preferably higher than 24, preferably higher than 25; and

[0268] -The electrical conductivity in MS / m and hardness HK 0.05 conform to the following relationship:

[0269] 39<[conductivity+(0.137×hardness)]<47; and preferably

[0270] 40<[conductivity+(0.137×hardness)]<46; and more preferably

[0271] 41<[conductivity+(0.137×hardness)]<45.

[0272] Example 2: Counterexample

[0273] Additional tests were carried out under the same conditions as in Example 1 above. The alloys of Table 6 were tested (casting followed by rapid prototyping) and then subjected to Knoop hardness measurements under a load of 50 g, both in the original state and after additional heat treatment at 400°C for different lengths, and electrical conductivity measurements (see Table 7).

[0274] [Table 6]

[0275] Composition No. type Fe Zr Ce La Ti Mn V 6 invention 1.00 1.20 0.75 0.75 24 Compare 1.00 1.20 1.00 25 Compare 2.00 1.20 2.00 26 Compare 2.00 1.20 2.00 27 Compare 1.00 1.20 1.00

[0276] [Table 7]

[0277]

[0278]

[0279] The results of the above experiments make it possible to prove that the choice of the essential elements of the invention is not a coincidence but is justified by the technical effect, which makes it possible to solve the compromise between hardness and conductivity.

[0280] Example 1 makes it possible to demonstrate that the essential elements according to the invention enable the technical problem of achieving a good compromise between hardness and electrical conductivity to be solved.

[0281] The additional tests of Example 2 made it possible to demonstrate that it is not possible to obtain a good compromise if one of the essential elements is excluded and if it is replaced by another element, such as Ti, Mn or V. In fact, the compromise achieved with the composition according to the invention (No. 6 above and Tables 2 to 5) is better than that achieved with the comparative compositions (Nos. 24 to 27), since the conductivity of the comparative compositions is always lower than that of the compositions according to the invention and their hardness after heat treatment tends to be worse.

Claims

1. A method for manufacturing a part (20), the method comprising forming successive metal layers (201 ... 20 n ), each layer being formed by depositing a filler metal (15, 25) to which energy is input so as to melt and to form the layer when solidified, the method being characterized in that the filler metal (15, 25) is an aluminum alloy containing the following alloying elements (in weight %): at least one alloying element selected from Zr, Hf and Er, the mass fraction of which individually and in total is greater than or equal to 0.30%, preferably from 0.30 to 2.50%, preferably from 0.40 to 2.00%, More preferably 0.40 to 1.80%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%; - at least one alloying element selected from Co, La, Ce, mischmetal, W, Ta, Mo and Nb, the mass fractions of which are each and in total at least 0.10%, preferably at least 0.25%, more preferably at least 0.50%; and the mass fractions of which are each less than 5.00%, Preferably less than 4.00%, preferably less than 3.00%; and the total mass fraction thereof is less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%; - optionally Fe, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, Preferably 0.10 to 1.00%, preferably 0.10 to 0.70%; - optionally Si, the mass fraction of which is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%, Preferably less than 0.20%, preferably less than 0.10%; - optionally Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%, Preferably less than 0.20%, preferably less than 0.10%; - optionally at least one alloying element chosen from Cr, V, Ti and Mn, the mass fractions of which are each less than 0.50%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%, more preferably less than 0.05% and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than 0.50%, more preferably less than 0.10%, even more preferably less than 0.05%; - optionally Mg, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%; - optionally Zn, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%; - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%; - optionally at least one selected from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, The mass fraction of the elements Ca, P, B, In and Sn is less than or equal to 1.00% each, Preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm, and a total of less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%, Preferably less than or equal to 0.30%; - Impurities: <0.05% each and <0.15% in total; The rest is aluminum.

2. A method of manufacturing a part, the method comprising forming successive metal layers superimposed on each other, each layer being formed by depositing a filler metal which melts after energy input and forms the layer when solidified, the method being characterized in that the filler metal is an aluminum alloy containing the following alloying elements (in weight percentages): at least one alloying element selected from Zr, Hf and Er, the mass fraction of which individually and in total is greater than or equal to 0.30%, preferably from 0.30 to 2.50%, preferably from 0.40 to 2.00%, More preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%; -Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, Preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%; and its mass fraction is greater than 500ppm, preferably greater than 0.10%, preferably greater than 0.15%, preferably greater than 0.20%; - optionally at least one alloying element selected from Co, La, Ce, mischmetal, W, Ta, Mo and Nb, the mass fractions of which individually and in total are at least 0.10%, Preferably at least 0.25%, more preferably at least 0.50%; and their mass fractions are each less than 5.00%, preferably less than 4.00%, preferably less than 3.00%; and their mass fractions are less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00% in total; - optionally Fe, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, Preferably 0.10 to 1.00%, preferably 0.10 to 0.70%; - optionally Si, the mass fraction of which is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%, Preferably less than 0.20%, preferably less than 0.10%; - optionally at least one alloying element chosen from Cr, V, Ti and Mn, the mass fractions of which are each less than 0.50%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%, more preferably less than 0.05% and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than 0.50%, more preferably less than 0.10%, even more preferably less than 0.05%; - optionally Mg, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.10%. Preferably less than 0.05%; - optionally Zn, with a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.10% Preferably less than 0.05%; - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%; - optionally at least one selected from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, The mass fraction of the elements Ca, P, B, In and Sn is less than or equal to 1.00% each, Preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm, and a total of less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%, Preferably less than or equal to 0.30%; - Impurities: <0.05% individually and preferably <0.15% in total; The rest is aluminum.

3. The method according to any one of the preceding claims, comprising forming a layer (201 ... 20 n ), i.e. after the final part is formed, a post-manufacturing heat treatment is applied, preferably tempering or annealing.

4. A method according to any one of the preceding claims, wherein no solution treatment and / or quenching is performed after forming the layer, ie after forming the final part, or after post-manufacturing heat treatment.

5. A method according to any one of the preceding claims, characterised in that This is carried out at a preheating temperature T of up to 500°C.

6. A method according to any one of the preceding claims, wherein the filler metal is in the form of a powder (15) which is exposed to a light beam (12) or a charged particle beam, causing local melting and then solidification, thereby forming a solid layer (201 ... 20 n ).

7. A method according to any one of claims 1 to 5, wherein the filler metal originates from a filler wire (25) which is exposed to a heat source (22) causing local melting and then solidification to form a solid layer (201 ... 20 n ).

8. Metal part obtained by the method object according to any of the preceding claims.

9. The metal part according to claim 8, characterized in that: After post-treatment at 400°C for 4 hours: - an electrical conductivity in MS / m higher than 20, preferably higher than 22, preferably higher than 23, Preferably higher than 24, preferably higher than 25; and -The electrical conductivity in MS / m and hardness HK 0.05 conform to the following relationship: 38<[conductivity+(0.137×hardness)]<47; and preferably 39<[conductivity+(0.137×hardness)]<46; and more preferably 40<[conductivity+(0.137×hardness)]<45.

10. The metal part according to claim 8, characterized in that After post-treatment at 400°C for 4 hours: - an electrical conductivity in MS / m higher than 20, preferably higher than 22, preferably higher than 23, Preferably higher than 24, preferably higher than 25; and -The electrical conductivity in MS / m and hardness HK 0.05 conform to the following relationship: 39<[conductivity+(0.137×hardness)]<47; and preferably 40<[conductivity+(0.137×hardness)]<46; and more preferably 41<[conductivity+(0.137×hardness)]<45.

11. A powder intended for use as a filler material in an additive manufacturing process, characterized in that It is formed from an aluminum alloy containing the following alloying elements (in wt. %): at least one alloying element selected from Zr, Hf and Er, the mass fraction of which individually and in total is greater than or equal to 0.30%, preferably from 0.30 to 2.50%, preferably from 0.40 to 2.00%, More preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%; - at least one alloying element selected from Co, La, Ce, mischmetal, W, Ta, Mo and Nb, the mass fractions of which are each and in total at least 0.10%, preferably at least 0.25%, more preferably at least 0.50%; and the mass fractions of which are each less than 5.00%, Preferably less than 4.00%, preferably less than 3.00%; and the total mass fraction thereof is less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00%; - optionally Fe, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, Preferably 0.10 to 1.00%, preferably 0.10 to 0.70%; - optionally Si, the mass fraction of which is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%, Preferably less than 0.20%, preferably less than 0.10%; - optionally Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%, Preferably less than 0.20%, preferably less than 0.10%; - optionally at least one alloying element chosen from Cr, V, Ti and Mn, the mass fractions of which are each less than 0.50%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%, more preferably less than 0.05%, and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than 0.50%, more preferably less than 0.1%, even more preferably less than 0.05%; - optionally Mg, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%; - optionally Zn, in a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%; - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%; - optionally at least one selected from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, The mass fraction of the elements Ca, P, B, In and Sn is less than or equal to 1.00% each, Preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm, and a total of less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%, Preferably less than or equal to 0.30%; - Impurities: <0.05% each and <0.15% in total; The rest is aluminum.

12. A powder intended for use as a filler material in an additive manufacturing process, characterized in that It is formed from an aluminum alloy containing the following alloying elements (in wt. %): at least one alloying element selected from Zr, Hf and Er, the mass fraction of which individually and in total is greater than or equal to 0.30%, preferably from 0.30 to 2.50%, preferably from 0.40 to 2.00%, More preferably 0.40 to 1.80%, even more preferably 0.50 to 1.60%, even more preferably 0.60 to 1.50%, even more preferably 0.70 to 1.40%, even more preferably 0.80 to 1.30%; -Sc, whose mass fraction is less than 0.80%, preferably less than 0.70%, preferably less than 0.60%, Preferably less than 0.50%, preferably less than 0.40%, preferably less than 0.30%; and Its quality The amount fraction is greater than 500 ppm, preferably greater than 0.10%, preferably greater than 0.15%, preferably greater than 0.20%; - optionally at least one alloying element selected from Co, La, Ce, mischmetal, W, Ta, Mo and Nb, the mass fractions of which individually and in total are at least 0.10%, Preferably at least 0.25%, more preferably at least 0.50%; and their mass fractions are each less than 5.00%, preferably less than 4.00%, preferably less than 3.00%; and their mass fractions are less than 7.00%, preferably less than 6.00%, preferably less than 5.00%, preferably less than 4.00% in total; - optionally Fe, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally Ni, whose mass fraction is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; - optionally at least one alloying element selected from Cu and Ag, the mass fractions of which are individually and in total 0.10 to 3.00%, preferably 0.10 to 2.00%, preferably 0.10 to 1.60%, Preferably 0.10 to 1.00%, preferably 0.10 to 0.70%; - optionally Si, the mass fraction of which is less than 3.00%, preferably less than 2.00%, preferably less than 1.00%, preferably less than 0.50%; in one embodiment, the Si content is less than 0.30%, Preferably less than 0.20%, preferably less than 0.10%; - optionally at least one alloying element chosen from Cr, V, Ti and Mn, the mass fractions of which are each less than 0.50%, preferably less than 0.30%, preferably less than 0.20%, preferably less than 0.10%, more preferably less than 0.05%, and in total less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than 0.50%, more preferably less than 0.1%, even more preferably less than 0.05%; - optionally Mg, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.10%. Preferably less than 0.05%; - optionally Zn, with a mass fraction of less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.10% Preferably less than 0.05%; - optionally Li, whose mass fraction is less than 2.00%, preferably less than 1.00%, preferably less than 0.50%, more preferably less than 0.30%, even more preferably less than 0.10%, even more preferably less than 0.05%; - optionally at least one selected from Nd, Y, Tm, Lu, Yb, Sr, Ba, Sb, Bi, The mass fraction of the elements Ca, P, B, In and Sn is less than or equal to 1.00% each, Preferably less than or equal to 0.50%, preferably less than or equal to 0.30%, more preferably less than or equal to 0.10%, even more preferably less than or equal to 700 ppm, and a total of less than or equal to 2.00%, preferably less than or equal to 1.00%, preferably less than or equal to 0.50%, Preferably less than or equal to 0.30%; - Impurities: <0.05% each and <0.15% in total; The rest is aluminum.

13. Use of the powder according to claim 11 or 12 for a manufacturing method, wherein the manufacturing method is selected from the following: EBM (electron beam melting), cold spraying (CSC or CS), laser melting deposition (LMD), additive friction manufacturing (AFS or AFSD, or FSAM, or FS), spark plasma sintering (FAST) or rotational friction welding (IRFW), preferably cold spraying (CSC).

Citation Information

Patent Citations

  • Method of manufacturing aluminum alloy articles

    US20170016096A1

  • Methods for producing forged products and other worked products

    WO2015006447A1